The Anticipatory, Short-Term, and Long-Term Effects of Parental Separation and Parental Death on Adolescent Delinquency - Kroese, Janique (Journal of developmental and life-course criminology, 2024)
Studies investigating the role of single-parent families in adolescent delinquency have seldom differentiated between types of single-parent families. Furthermore, they have typically assumed that parental disruption is a discrete event marking an abrupt change between dual-parenthood and single-parenthood. Using Dutch longitudinal population register data, we estimated fixed-effects panel models to assess (1) whether the event of parental disruption, either by parental separation or by parental death, increases subsequent adolescent delinquency and (2) whether parental disruption, either by parental separation or by parental death, has anticipatory, immediate, or delayed effects on adolescent delinquency. Our results showed that both parental separation and parental death seem to boost adolescent delinquency, and we found no difference between these types of single-parent families. However, when distinguishing between anticipatory, short-term, and long-term effects, we found a short-term increase in adolescent delinquency after a parental separation and an anticipatory reduction in adolescent delinquency before a parental death. Future research should pay more attention to diversity in the composition of single-parent families, as well as to the anticipatory, short-term, and long-term consequences.